2007
DOI: 10.1097/01.aog.0000254165.92653.e8
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Incidence in a Prevaccine Era in the United States, 1998–2002

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
76
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 21 publications
11
76
0
4
Order By: Relevance
“…NH black, API, AI/AN, and Hispanic women each account for a larger proportion of cervical cancer survivors than breast or colorectal cancer survivors. Higher rates of cervical cancer among non-white women are well documented and are often attributed to differences in Pap testing, including treatment of pre-invasive disease and follow-up of abnormal test results [19][20][21][22]. We also found that women diagnosed with cervical cancer have the highest risk of developing a subsequent tobacco-related malignancy over a 15-year period immediately following diagnosis, which then decreases to risks similarly observed in other cancer survivors.…”
Section: Discussionsupporting
confidence: 55%
“…NH black, API, AI/AN, and Hispanic women each account for a larger proportion of cervical cancer survivors than breast or colorectal cancer survivors. Higher rates of cervical cancer among non-white women are well documented and are often attributed to differences in Pap testing, including treatment of pre-invasive disease and follow-up of abnormal test results [19][20][21][22]. We also found that women diagnosed with cervical cancer have the highest risk of developing a subsequent tobacco-related malignancy over a 15-year period immediately following diagnosis, which then decreases to risks similarly observed in other cancer survivors.…”
Section: Discussionsupporting
confidence: 55%
“…[14][15][16] The NBCCEDP has been able to reach populations (eg, African Americans, Hispanics, and American Indians/Alaska Natives) whose rates of screening fall far below national averages. A variety of successful recruitment strategies has made inroads in educating women about the importance of screening, explaining the services available, removing barriers to screening, and motivating women to complete screening exams as part of their routine healthcare.…”
Section: The National Breast and Cervical Cancer Early Detection Progmentioning
confidence: 99%
“…The global annual incidence was estimated at 528,000 cases, and the annual number of CC‐related deaths was estimated at 266,000 1, 2. In the United States, CC is the third most common genital tract malignancy and approximately 12,042 new cases and 4074 deaths were attributed to this disease in 2012 2, 3.…”
Section: Introductionmentioning
confidence: 99%
“…The global annual incidence was estimated at 528,000 cases, and the annual number of CC‐related deaths was estimated at 266,000 1, 2. In the United States, CC is the third most common genital tract malignancy and approximately 12,042 new cases and 4074 deaths were attributed to this disease in 2012 2, 3. In the past 40 years, as a result of increased surveillance and improved treatment 2, 3, both the incidence and mortality of CC have significantly decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation